Factors that Hinder the Development of EFL Learners’ Speaking Skill - Zainab Nizar Karam; Mowafaq Muhammed Al Kassab (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Nowadays, the inclusive expansion of the English language has led to the importance of mastering four skills of the language, in particular the speaking skill. Despite the importance of the speaking skill, a large number of EFL learners still have issues in communicating and using the language whether inside their classrooms or in their daily lives. Hence, a quantitative study was designed to investigate the factors that can impede the improvement of the speaking skill of EFL learners. The study included 92 participants from Tishk International University (TIU) studying in Education, Pharmacy, Nursing, and Medical Analysis faculties. The results of the questionnaire showed that motivation, personality, attitudes towards English language teachers (AET), classroom environment and instructional media (CEIM), and attitudes towards English language (ATEL) have a significant difference towards the improvement of the speaking skills. The results of this study will have a number of pedagogical implications for teachers, policy makers, as well as curriculum design.